“It’s Always Been a Second Class Cancer”: An Exploration of the Experiences and Journeys of Bereaved Family Carers of People with Sarcoma - O’Connor, M.; Smith, G.; Pantaleo, A.; Haywood, D.; Weaver, R.; Halkett, Georgia (MDPI, 2021)
Sarcomas are a group of rare and aggressive cancers, which develop in bones and connec-tive tissue throughout the body. Sarcomas account for only 1–2% of all cancers worldwide; however, mortality rates for sarcoma are high with approximately two in four sarcoma patients dying following a diagnosis. Delays in diagnosis, poor management of symptoms, patients’ high symptom loads and high carer burden are all associated with carer distress, which may lead to complications after bereavement. The experience of having a family member referred for palliative care is also distress-ing for carers, with the realisation that their family member is dying. This study aimed to explore the experiences of bereaved family carers of people diagnosed with sarcoma. A qualitative descriptive design using a social constructionist framework was adopted. Interviews were conducted with sixteen participants, and thematic analysis was used to identify patterns in the data. Four overarch-ing themes emerged: beginning the journey; moving through treatment; transitioning to palliative care; and experiencing bereavement. The narratives were coherent and potent, and people reflected on their journeys. Interventions and supports for bereaved carers could include opportunities for counselling to support reflections, supports for developing a narrative such as writing therapy, and preparation for the death of the family member.